2007
DOI: 10.1093/ajcn/85.3.724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a reduced-glycemic-load diet on body weight, body composition, and cardiovascular disease risk markers in overweight and obese adults

Abstract: These findings provide evidence that an ad libitum RGL diet is a reasonable alternative to a low-fat, portion-controlled eating plan for weight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 46 publications
4
82
2
Order By: Relevance
“…Concerning the effects of GL on body composition, little information is currently available because most trials of dietary GL have reported only changes in body weight [1,2,[4][5][6]8]. One short-term study detected a non-significant trend toward a relative increase in nitrogen accretion in individuals consuming a LG diet compared to a HG diet [15], a finding consistent with a study in animals indicating relatively greater fat mass and lesser FFM after consumption of a HG diet compared [27] to a LG diet.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Concerning the effects of GL on body composition, little information is currently available because most trials of dietary GL have reported only changes in body weight [1,2,[4][5][6]8]. One short-term study detected a non-significant trend toward a relative increase in nitrogen accretion in individuals consuming a LG diet compared to a HG diet [15], a finding consistent with a study in animals indicating relatively greater fat mass and lesser FFM after consumption of a HG diet compared [27] to a LG diet.…”
Section: Introductionmentioning
confidence: 62%
“…Both total carbohydrate and carbohydrate type (as quantified by the GL and GI, respectively) have been studied for their effects on hunger and satiety [42][43][44][45], and weight loss and prevention of weight gain [5][6][7]10,46]. Single-meal and other shortterm studies generally document beneficial effects of low carbohydrate diets and low GI diets on hunger and satiety [43,44], but most longer-term studies have reported no significant difference in weight loss or weight regain [5][6][7]10]. Given the ongoing lack of consensus in this area, we evaluated the effects of HG and LG diets on metabolic adaptation and body composition change, reasoning that a finding of differences in these parameters could contribute to the ongoing debate about optimal carbohydrate intake for long-term weight control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet A had the highest GL (diet records: 129 g) and diet D the lowest GL (59 g) Diet records and monitoring of 10 h glucose and insulin responses indicated that substantial contrasts in GI and GL existed between the diets. Fiber intake was substantially higher for diet B than for the other diets Diet A: weight À3.7, fat À2.8 kg; diet B: weight À4.8, fat À4.5 kg; diet C: weight À5.3, fat À4.3 kg; diet D: weight À4.4, fat À3.7 kg P ¼ 0.17 for differences in weight and P ¼ 0.08 for differences in fat mass (Maki et al, 2007) US F/M, age 18-65 waist X87 cm for women and X90 cm for men. Low GL: n ¼ 43, control diet: n ¼ 43. n ¼ 10 and 7 lost to follow-up, but all except 1 for both groups included in intention to treat for weight (last observation carried forward) 36 weeks starting with 12-24 weeks weigh loss phase followed by weight maintenance.…”
Section: Cohort Studies Of the Gi And Glmentioning
confidence: 92%
“…Diets rich in foods with a high glycaemic index have been associated with an increased risk of diabetes [73], heart disease [74,75], and obesity [76,77], and there are ongoing studies linking diets with a high glycaemic index with age-related macular degeneration [78], ovulatory infertility [79], and colorectal cancer [80]. In this context, energy-restricted diets with a lower glycaemic index can improve energy adaptation during obesity treatment, favouring weight loss and improving lipid (total cholesterol and LDL cholesterol) and glycaemic (insulin and glucose) profiles [81].…”
Section: Diet and Healthmentioning
confidence: 99%